The Dark Side of Artificial Intelligence: Psychological Distress and Artificial Intelligence Dependence as Serial Mediators Between Self-Control and Subjective Vitality - Kara, Berkan Can (SPRINGER, 2026)
Since the emergence of artificial intelligence (AI) tools, they have rapidly become widespread in both individual and corporate domains. Despite offering numerous benefits, the uncontrolled use of these tools brings various risks to the forefront. Therefore, examining AI dependence and related variables is of great importance. However, studies conducted on this topic in the literature are quite limited. The present study aims to examine the serial mediating role of psychological distress and AI dependence in the relationship between self-control (SC) and subjective vitality (SV). The sample of the study consists of 701 adult individuals residing in T & uuml;rkiye, representing various occupational groups and ranging in age from 18 to 60 years (61.34% female, Mage = 29.50 years, SD = 8.61). A two-step SEM approach was employed, and indirect effects were examined using bootstrapping analysis. The findings suggest that psychological distress and AI dependence may play a serial mediating role in the relationship between SC and SV. The present study offers a unique contribution to the holistic understanding of the relationship between AI technologies, personality traits, and individual well-being. The results of the study are expected to contribute to increasing awareness regarding excessive use of AI and to the development of interventions and preventive efforts aimed at reducing such usage. Based on the findings, interventions aimed at strengthening self-control and reducing psychological distress may help prevent excessive AI use and support subjective vitality.
Keywords: Self-control; Psychological distress; Artificial intelligence dependence; Subjective vitality; Serial mediation model; MODEL; ADDICTION; MOTIVATIONS; DEPRESSION; STRATEGIES; ANXIETY; HEALTH; ROLES; Psychology; Substance Abuse; Psychiatry